PEMANTAUAN GUNUNG TANGGAMUS BERSAMA ANGGOTA KOPASUS TNI-AD - Andreas Andoyo; Riki Renaldo (Jurnal PkM Pemberdayaan Masyarakat, 2020)
Climbing activities carried out by the Army Special Forces Kopasus team in collaboration with STMIK Pringsewu and the community on the slopes of Mount Tanggamus provide learning values ​​for young people, the community about the importance of preserving nature in order to stay sustainable and protecting the ecosystem in it. This activity which involves students and the community provides information on how humans need nature as energy and food resources. Besides that, understanding insights on nature preservation for the community will have an impact on the preservation of nature in the Tanggamus Regency